2010
DOI: 10.1016/j.ijpara.2009.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of Echinococcus tapeworms in China as determined by mitochondrial and nuclear DNA sequences

Abstract: The genetic polymorphisms of Echinococcus spp. in the eastern Tibetan Plateau and the Xinjiang Uyghur Autonomous Region were evaluated by DNA sequencing analyses of genes for mitochondrial cytochrome c oxidase subunit 1 (cox1) and nuclear elongation factor-1 alpha (ef1a). We collected 68 isolates of Echinococcus granulosus sensu stricto (s.s.) from Xinjiang and 113 isolates of E. granulosus s. s., 49 isolates of Echinococcus multilocularis and 34 isolates of Echinococcus shiquicus from the Tibetan Plateau. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
110
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(140 citation statements)
references
References 37 publications
27
110
3
Order By: Relevance
“…This sequence type is the most commonly recorded G1 variant in southern Palearctic and it was previously recorded in China (Qinghai province) in sheep [33], in Russia (Altai region) in human [34], in Mongolia in human (GenBank Accession No. AB787538, unpublished), in Turkey in sheep, cattle and human [20,35], in Iran in sheep, human, camel and goat [36] and GenBank Accession No.…”
Section: Resultsmentioning
confidence: 62%
“…This sequence type is the most commonly recorded G1 variant in southern Palearctic and it was previously recorded in China (Qinghai province) in sheep [33], in Russia (Altai region) in human [34], in Mongolia in human (GenBank Accession No. AB787538, unpublished), in Turkey in sheep, cattle and human [20,35], in Iran in sheep, human, camel and goat [36] and GenBank Accession No.…”
Section: Resultsmentioning
confidence: 62%
“…Subsequently, much more comprehensive analyses of mtDNA variation in E. granulosus from the Middle East, Europe, China, South Asia, Africa, South America and Australia have found relatively low levels of nucleotide diversity, although greater levels of haplotype diversity, again suggesting rapid population expansion from small founder populations Nakao et al, 2010b;Casulli et al, 2012;Yanagida et al, 2012;Sharma et al, 2013). A comparison of haplotype diversities suggests a Middle Eastern origin for this species (or at least for the switch from a wildlife to a domestic host cycle), with subsequent spread to other parts of the world through anthropogenic transport of hosts (Nakao et al, 2013b).…”
Section: Genetic Diversity Within Populations Reflects Time Since Colmentioning
confidence: 99%
“…Nakao et al (2010b) found low levels of mtDNA diversity in E. multilocularis in the Tibetan Plateau and suggested that the species was introduced to this region by a recent range extension of the red fox (Vulpes vulpes), although this hypothesis requires confirmation because there does not seem to be independent evidence of such a range extension (Kutschera et al, 2013). However, relatively high levels of mtDNA diversity have been found for E. shiquicus in the Tibetan Plateau (Nakao et al 2010b) and E. vogeli in Brazil (Santos et al 2012). Both E.…”
Section: Genetic Diversity Within Populations Reflects Time Since Colmentioning
confidence: 99%
See 1 more Smart Citation
“…This was the first study to describe the existence of EG senso estricto (G3) in South America and to verify that goats act as a reservoir of E. canadensis (G6) in Neuquén (Soriano et al). Nakao et al (2010), of the Department of Parasitology at Asahikawa Medical College in Hokkaido, Japan, investigated the genetic polymorphisms of Echinococcus spp. in the eastern part of the Tibetan plateau and the Region of Xinjiang, applying a DNA sequencing analysis to the mitochondrial COI and nuclear elongation factor-1 alpha.…”
Section: Available Evidencementioning
confidence: 99%